The Christian and Climate Change: lutheran ethics between Creation and New Creation - Gatsk, Aline Weimann; Stahlhoefer, Alexander De Bona (Vox Scripturae - Revista Teológica Internacional, 2025)
This article proposes a concise approach to the ethical-environmental position of Christians regarding the issue of climate change, which raises various theological questions within a so-called eschatological horizon, that is, one that values and considers fundamental its place within the integrable dimensions of Creation and New Creation. First, we seek to present a brief overview of the main ethical-environmental discussions today, from those in the secular sphere to those that are specifically Christian. Secondly, we propose to address three texts by the reformer Martin Luther that deal with the theme of Creation, more specifically texts referring to the book of Genesis and the Epistle to the Romans 8.19-25. Next, a more detailed approach is taken to the reception of Luther's Theology of Creation by the Lutheran theologian Oswald Bayer, which is not restricted to the reformer, but also includes related contributions from the so-called philologist of the cross, Johann Georg Hamann. Finally, a critical analysis is proposed of some theological points from various documents published by or linked to the Evangelical Church of Lutheran Confession in Brazil (IECLB) that address environmental issues, notably the challenges posed by climate change, in order to motivate the search for ways to continue this reflection.
Keywords: Climate change; Lutheran ethics; Eschatology